2014
DOI: 10.1590/s1517-83822014000300014
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of non-LEE-encoded type 3 secretion system dependent effectors in enteropathogenic Escherichia coli

Abstract: Enteropathogenic Escherichia coli (EPEC) are important human gastroenteritis agents. The prevalence of six non-LEE genes encoding type 3 translocated effectors was investigated. The nleC, cif and nleB genes were more prevalent in typical than in atypical EPEC, although a higher diversity of genes combinations was observed in atypical EPEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
4
9
0
1
Order By: Relevance
“…Four principle results emerged from our data: (1) the OI-122 modules were found in all tEPEC (except one isolate), but the levels of distribution varied among the OI-122 modules observed within isolates, (2) more aEPEC (57.7%) lake of OI-122 genes and the OI-122 modules was prevalent in tEPEC than in aEPEC isolates, (3) there was statistical evidence for the existence of nleB, efa/lifA, sen and pagC genes in tEPEC genotype, and (4) there was a high degree of genetic heterogeneity among OI-122 carrying EPEC strains. These results were consistent with those previously reported; suggesting that the acquisition of complete OI-122 island, OI-122 module, and OI-122 genes are evidence of horizontal gene transfer and the evolutionary dynamics among EPEC strains (5,15). While obtained of the OI-122 genes are associated with severe diseases and outbreaks (6), our results could not indicate the association between OI-122 module and severity of disease because all of the strains analyzed in this study were isolated from children with acute diarrhea.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Four principle results emerged from our data: (1) the OI-122 modules were found in all tEPEC (except one isolate), but the levels of distribution varied among the OI-122 modules observed within isolates, (2) more aEPEC (57.7%) lake of OI-122 genes and the OI-122 modules was prevalent in tEPEC than in aEPEC isolates, (3) there was statistical evidence for the existence of nleB, efa/lifA, sen and pagC genes in tEPEC genotype, and (4) there was a high degree of genetic heterogeneity among OI-122 carrying EPEC strains. These results were consistent with those previously reported; suggesting that the acquisition of complete OI-122 island, OI-122 module, and OI-122 genes are evidence of horizontal gene transfer and the evolutionary dynamics among EPEC strains (5,15). While obtained of the OI-122 genes are associated with severe diseases and outbreaks (6), our results could not indicate the association between OI-122 module and severity of disease because all of the strains analyzed in this study were isolated from children with acute diarrhea.…”
Section: Discussionsupporting
confidence: 93%
“…A complete OI-122 gene (carrying efa1/lifA, pagC, sen, and nleB) was more prevalent in tEPEC (18.75%) than in aEPEC (3.84%). Similar results were reported by Vieira et al and Salvador et al (5,15).…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of non‐LEE encoded effectors is more varied. NleC appears frequently among EPEC strains, whereas NleE, NleB and Cif appear in approximately half of EPEC isolates, while NleD is in fewer than half (Arbeloa et al ., ; Creuzburg et al ., ; Salvador et al ., ). With regard to effector activity, NleC, NleE, EspF and EspZ each mediate characteristic phenotypes during infection and play substantial roles in virulence, whereas NleF and NleD play contributory roles, but are not essential for virulence (Wickham et al ., ; Baruch et al ., ; Blasche et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, when trying to investigate whether some VRGs would correlate with tEPEC-or aEPEC-positive samples, we found that map, a gene located on the LEE, was the only one differently distributed between the two groups, being more prevalent in aEPEC isolates. Other studies have identified specific genetic markers associated with EPEC subtypes (39,40), showing that genes both located on the LEE and not located on the LEE could be associated with either tEPEC or aEPEC. In general, aEPEC bacteria show more variability than tEPEC bacteria (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have identified specific genetic markers associated with EPEC subtypes (39,40), showing that genes both located on the LEE and not located on the LEE could be associated with either tEPEC or aEPEC. In general, aEPEC bacteria show more variability than tEPEC bacteria (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%